Regional Differences in the Effects of Social Relations on Depression Among Korean Elderly and the Moderating Effect of Living Alone - Chanki Kim; Eun Jee Chang; Chang-yup Kim (Korean Society for Preventive Medicine, 2021)
Objectives Socioeconomic disadvantages interact with numerous factors which affect geriatric mental health. One of the main factors is the social relations of the elderly. The elderly have different experiences and meanings in their social lives depending on their socio-cultural environment. In this study, we compared the effects of social relations on depression among the elderly according to their living arrangement (living alone or living with others) and residential area. Methods We defined social relations as "meetings with neighbors" (MN). We then analyzed the impact of MN on depression using data from the Korean Longitudinal Study of Aging Panel with the generalized estimating equation model. We also examined the moderating effect of living alone and performed subgroup analysis by dividing the sample according to which area they lived in. Results MN was associated with a reduced risk of depressive symptoms among elderlies. The size of the effect was larger in rural areas than in large cities. However, elderly those who lived alone in rural areas had a smaller protective impact of MN on depression, comparing to those who lived with others. The moderating effect of living alone was significant only in rural areas. Conclusions The social relations among elderlies had a positive effect on their mental health: The more frequent MN were held, the less risk of depressive symptoms occurred. However, the effect may vary depending on their living arrangement and environment. Thus, policies or programs targeting to enhance geriatric mental health should consider different socio-cultural backgrounds among elderlies.